Cultural backlash : Trump, Brexit, and the rise of authoritarian-populism - Norris, Pippa (Cambridge University Press, 2018)
"Preface and acknowledgments: The intellectual foundations for this study build upon a collaborative partnership developed over many years, producing a series of earlier books jointly written by the authors for Cambridge University Press which have compared gender equality in politics, political communications, and religion around the world. Pippa Norris's research for this study has been generously supported by the research award of the Kathleen Fitzpatrick Australian Laureate from the Australian Research Council. The Electoral Integrity Project is based at Harvard University's John F. Kennedy School of Government and the Department of Government and International Relations at the University of Sydney"--